Cost-effectiveness of subdermal implantable buprenorphine versus sublingual buprenorphine to treat opioid use disorder. (3rd August 2017) - Carter, John A.; Dammerman, Ryan; Frost, Michael
Abstract: Aims: Subdermal implantable buprenorphine (BSI) was recently approved to treat opioid use disorder (OUD) in clinically-stable adults. In the pivotal clinical trial, BSI was associated with a higher proportion of completely-abstinent patients (85.7% vs 71.9%; p = .03) vs sublingual buprenorphine (SL-BPN). Elsewhere, relapse to illicit drug use is associated with diminished treatment outcomes and increased costs. This study evaluated the cost-effectiveness of BSI vs SL-BPN from a US societal perspective. Methods: A Markov model simulated BSI and SL-BPN cohorts (clinically-stable adults) transiting through four mutually-exclusive health states for 12 months. Cohorts accumulated direct medical costs from drug acquisition/administration; treatment-diversion/abuse; newly-acquired hepatitis-C; emergency room, hospital, and rehabilitation services; and pediatric poisonings. Non-medical costs of criminality, lost wages/work-productivity, and out-of-pocket expenses were also included. Transition probabilities to a relapsed state were derived from the aforementioned trial. Other transition probabilities, costs, and health-state utilities were derived from observational studies and adjusted for trial characteristics. Outcomes included incremental cost per quality-adjusted-life-year (QALY) gained and incremental net-monetary-benefit (INMB). Uncertainty was assessed by univariate and probabilistic sensitivity analysis (PSA). Results: BSI was associated with lower total costs (−4, 386), more QALYs (+0.031), and favorable INMB at all willingness-to-pay (WTP) thresholds considered. Higher drug acquisition costs for BSI (+6, 492) were outpaced, primarily by reductions in emergency room/hospital utilization (−8, 040) and criminality (−1, 212). BSI was cost-effective in 89% of PSA model replicates, and had a significantly higher NMB at 50, 000/QALY (20, 783 vs 15, 007; p < .05). Conclusions: BSI was preferred over SL-BPN from a health-economic perspective for treatment of OUD in clinically-stable adults. These findings should be interpreted carefully, due to some relationships having been modeled from inputs derived from multiple sources, and would benefit from comparison with outcomes from studies that employ administrative claims data or a naturalistic comparative design.